Physical chemistry . (3rd ed.) - Mortimer, Robert G. (Academic Press/Elsevier, 2020)
1. Thermodynamics and the macroscopic description of physical systems. The behavior of gases and liquids -- Work, heat, and energy: the First law of thermodynamics -- The Second and Third laws of thermodynamics: entropy -- The thermodynamics of real systems -- Phase equilibrium -- The thermodynamics of solutions -- Chemical equilibrium -- The thermodynamics of electrical systems -- pt. 2. Dynamics. Gas kinetic theory: the molecular theory of dilute gases at equilibrium -- Transport processes -- The rates of chemical reactions -- Chemical reaction mechanisms I: rate laws and mechanisms -- Chemical reaction mechanisms II: catalysis and miscellaneous topics -- pt. 3. The molecular structure of matter. Classical mechanics and the old quantum theory -- The principles of quantum mechanics. I. De Broglie waves and the Schrödinger equation -- The principles of quantum mechanics. II. The postulates of quantum mechanics -- The electronic states of atoms. I. The hydrogen atom -- The electronic states of atoms. II. The zero-order approximation for multielectron atoms -- The electronic states of atoms. III. Higher-order approximations -- The electronic states of diatomic molecules -- The electronic structure of polyatomic molecules -- Translational, rotational, and vibrational states of atoms and molecules -- Optical spectroscopy and photochemistry -- Magnetic resonance spectroscopy -- pt. 4. The reconciliation of the macroscopic and molecular theories of matter. Equilibrium statistical mechanics. I. The probability distribution for molecular states -- Equilibrium statistical mechanics. II. Statistical thermodynamics -- Equilibrium statistical mechanics III. Ensembles -- The structure of solids, liquids, and polymers -- Appendices.